2010 IEEE International Systems Conference 2010
DOI: 10.1109/systems.2010.5482329
|View full text |Cite
|
Sign up to set email alerts
|

Topological analysis of the power grid and mitigation strategies against cascading failures

Abstract: Abstract-This paper presents a complex systems overview of a power grid network. In recent years, concerns about the robustness of the power grid have grown because of several cascading outages in different parts of the world. In this paper, cascading effect has been simulated on three different networks, the IEEE 300 bus test system, the IEEE 118 bus test system, and the WSCC 179 bus equivalent model. Power Degradation has been discussed as a measure to estimate the damage to the network, in terms of load los… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 36 publications
(47 reference statements)
3
45
0
5
Order By: Relevance
“…The resilience has been carried out in term of flow availability. In a similar approach, [172] makes use of power flow in the analysis of a synthetic (IEEE bus test system) high-voltage network with N = 550 nodes and M = 800 unweighted links. The resilience is assessed in terms of the influence in network connectivity and power degradation.…”
Section: Power Flow Models On Cn Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resilience has been carried out in term of flow availability. In a similar approach, [172] makes use of power flow in the analysis of a synthetic (IEEE bus test system) high-voltage network with N = 550 nodes and M = 800 unweighted links. The resilience is assessed in terms of the influence in network connectivity and power degradation.…”
Section: Power Flow Models On Cn Graphsmentioning
confidence: 99%
“…Link attack has been adopted in [35,152,155,169,172,184,188,192,193], which also include both topological-and hybrid-based approaches. There are a few works that have carried out both analyses [7,85,112,117,151,170].…”
Section: Removing/attacking Strategies To Perform Vulnerability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This failure had also a visible impact on the interrelated Internet infrastructure, affecting almost half of all Internet autonomous systems. Pahwa et al [9] used simulations to analyze the vulnerability of power grids to cascading failures. They found that careful post-failure load redistribution can help averting cascades.…”
Section: Correlated Cascading Failuresmentioning
confidence: 99%
“…In simple words, when one failure leads to successive failure of other elements of the grid, leading to huge losses, the process is called a cascading failure. Some strategies such as reciprocal altruism [5], changing the dynamic equilibrium of the system to a point of self-organized criticality [6], [11], and different load shedding schemes [7], [8], [9], [10] have been suggested in the past for reducing the effects of cascading failures.…”
Section: Introductionmentioning
confidence: 99%